Where there is pressure, there is motivation? The impact of challenge-hindrance stressors on employees’ innovation performance - Dou, Guoqin; Yang, Jinjuan; Yang, Lifeng; Liu, Bin; Yuan, Yunyun (Frontiers in Psychology, 2022)
Based on the conservation of resource theory, this paper explores the impact mechanism of the challenge and hindrance stressors on innovation performance, introduces emotional atmosphere as a mediation variable, and on this basis, it examines the moderating role of organizational climate on emotional atmosphere and innovation performance. A two-wave survey of 263 subordinates and 29 supervisors who come from multisource field offered support for our model. Results showed that challenge stressors have a positive effect on innovation performance, positive emotional atmosphere mediates the relationship between challenge stressors and innovation performance; hindrance stressors have a negative effect on innovation performance, and negative emotional atmosphere mediates the relationship between hindrance stressors and innovation performance. Organizational climate strengthens the positive relationship between positive emotional atmosphere and innovation performance and weakens the negative relationship between negative emotional atmosphere and innovation performance. This study enriches the existing literature by identifying the impact of stressors on employee innovation performance and has certain practical significance for optimizing the management of enterprises and improving employee innovation performance.